Analysis of dog serologic data reveals critical insights into the epidemiology of human coccidioidomycosis, 2012-2023 - Sykes, Jane (My University, 2024)
I completed my Applied Practice Experience (APE) at the California Department of Public Health (CDPH) under the supervision of Gail Sondermeyer-Cooksey, MPH. My work was conducted in collaboration with graduate students at the University of California-Berkeley School of Public Health. The CDPH conducts surveillance, investigation, control, and prevention of important infectious diseases in California, and consists of 4 sections: Disease Investigations (DIS), Vector-Borne Disease (VBDS), Veterinary Public Health (VPHS), and Surveillance and Statistics (SSS). Coccidioidomycosis is one of the most common infectious diseases reported to the agency (https://www.cdph.ca.gov/Programs/CID/DCDC/Pages/SSS.aspx). Gail Cooksey has been with the Branch since 2012 and has an MPH from the University of California, Berkeley with an emphasis on infectious diseases and vaccinology.
Keywords: Coccidioidomycosis